The Leuven Immunomodulatory Protocol Promotes T‐Regulatory Cells and Substantially Prolongs Survival After First Intestinal Transplantation. Issue 10 (12th May 2016) - Ceulemans, L. J.; Braza, F.; Monbaliu, D.; Jochmans, I.; De Hertogh, G.; Du Plessis, J.; Emonds, M.‐P.; Kitade, H.; Kawai, M.; Li, Y.; Zhao, X.; Koshiba, T.; et al.
Abstract : Intestinal transplantation (ITx) remains challenged by frequent/severe rejections and immunosuppression‐related complications (infections/malignancies/drug toxicity). We developed the Leuven Immunomodulatory Protocol (LIP) in the lab and translated it to the clinics. LIP consists of experimentally proven maneuvers, destined to promote T‐regulatory (Tregs)‐dependent graft‐protective mechanisms: donor‐specific blood transfusion (DSBT); avoiding high‐dose steroids/calcineurin‐inhibitors; and minimizing reperfusion injury and endotoxin translocation. LIP was tested in 13 consecutive ITx from deceased donors (2000–2014) (observational cohort study). Recipient age was 37 years (2.8–57 years). Five‐year graft/patient survival was 92%. One patient died at 9 months due to aspergillosis, another at 12 years due to nonsteroidal anti‐inflammatory drug–induced enteropathy. Early acute rejection (AR) developed in two (15%); late AR in three (23%); all were reversible. No chronic rejection (CR) occurred. No malignancies developed and estimated glomerular filtration rate remained stable post‐Tx. At last follow‐up (3.5 years [0.5–12.5 years]), no donor‐specific antibodies were detected and 11 survivors were total parenteral nutrition free with a Karnofsky score >90% in 8 recipients (follow‐up >1 years). A high frequency of circulating CD4 + CD45RA ‐ Foxp3 hi memory Tregs was found (1.8% [1.39–2.21]), comparable to tolerant kidney transplant (KTx) recipients and superior to stable immunosuppression (IS)‐KTx, KTx with CR, and healthy volunteers. In this ITx cohort we show that DSBT in a low‐inflammatory/pro‐regulatory environment activates Tregs at levels similar to tolerant‐KTx, without causing sensitization. LIP limits rejection under reduced IS and thereby prolongs long‐term survival to an extent not previously attained after ITx. Abstract : This article describes the excellent outcome after intestinal transplantation of an immunomodulatory protocol destined to promote Treg‐dependent graft‐protective mechanisms: donor‐specific blood transfusion, avoidance of high‐dose steroids/calcineurin inhibitors, and minimization of reperfusion injury and endotoxin translocation.